Dragonfly falling ebook - Tchaikovsky, Adrian (Shadows of the Apt, 2009)
Dragonfly Falling is the second book in the critically acclaimed epic fantasy series Shadows of the Apt by Adrian Tchaikovsky, author of the Arthur C. Clarke Award-winning Children of Time. Every hero must be tested . . . The Wasp Empire's armies are on the move – and the city of Tark will be first to feel their might. Salma and Totho prepare for battle, alongside their Ant-kinden brethren. And within Tark's walls, they'll face a force greater than any Lowlander has ever seen. Stenwold Maker predicted this threat, and the Empire's secret service now deems him too dangerous to live. So he's to be eliminated, and his beloved city of Collegium destroyed. For if this centre of learning is lost, it will crush Lowland resistance. As the Empire's troops continue their relentless advance, their young Emperor pursues another, even darker goal. And his success would trigger a reign of blood lasting a thousand years. Dragonfly Falling is followed by the third book in the Shadows of the Apt series, Blood of the Mantis.